HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG KESEHATAN REPRODUKSI DENGAN KECEMASAN DALAM MENGHADAPI PREMENSTRUASI SYNDROME - Sri Wulan; Basyariah Lubis; Novita Br Ginting Munthe; Iskandar Markus Sembiring; Rahmad Gurusinga (JURNAL KESMAS DAN GIZI (JKG), 2021)
Premenstrual syndrome is a group of symptoms that occur in the luteal phase of the menstrual cycle that cause disruption to a person's work and lifestyle. Premenstrual syndrome makes women unable to function normally and requires treatment. This situation causes a decrease in the quality of life of women, for example students who experience premenstrual syndrome cannot concentrate on learning and their motivation to learn decreases because of the pain they feel. The purpose of this study was to determine the relationship between knowledge of young women and anxiety when facing premenstrual syndrome. This type of research is analytic by using a cross-sectional design. The population in this study were all female students in grades VII and VIII at SMP Negeri 1 Merbau in the 2020-2021 school year with a total population of 147 students and the sample in this study was 67 students who were taken by simple random sampling technique. Data analysis with chi-square test. The results of the analysis show that there is a relationship between knowledge about reproductive health and anxiety in dealing with premenstrual syndrome with a p value of 0.000. It is recommended for health services to be able to hold counseling about premenstrual syndrome to increase the knowledge of young women about premenstrual syndrome.